Cultural Heritage and Wind Turbines – A Method to Reduce Conflicts in Landscape Planning and Management: Studies in the German Ore Mountains - Wieduwilt, Patrick; Wirth, Peter (European countryside, 2018)
Landscape policy, management and planning can be interpreted as involving a dualism of conservation and transformation goals. Serious conflicts can emerge when conservation and development goals are contradictory. This paper reflects on the goal conflict between the establishment of a world heritage destination with 39 individual elements and the development of wind power facilities in the German Ore Mountains. In order to meet these challenges, the authors created a GIS-based so-called “Multiple-Visual-Link Method”. By calculating viewsheds with a tailor-made GIS application and defining distance zones (short, middle, long), the user is able to estimate the visual relations between the two types of subjects in a bigger area with a favorable cost-benefit relation. The compact algorithmic approach leads to solid results which can be translated into planning recommendations. There is also potential for it to be applied to similar goal conflicts.